Our actions are our future – a zero hunger world by 2030 is possible - Rahman, Habibur; Vijayalakshmy, Kennady (Indian Farming, 2018)
The main objective of ILRI is to create awareness among poor livestock farmers regarding various activities and methodologies which can be done to enhance the productivity. Hunger is an essential key factor which has to be taken into consideration when it comes to Global development. To erradicate hunger, the primary factor which has to be taken care is poverty. Eradication of poverty helps in the easy achievement of Zero Hunger. When it comes to poverty, small-scale livestock farmers are the ones which are most affected. Hence, various extension and research activities have to be taken care off in educating the small-scale livestock farmers regarding the enhancement of productivity. This helps them to gain more income and to eliminate poverty, which further helps them to have an access to highly nutritious food. If all these factors are taken care off, achievement of Zero Hunger by 2030 is highly possible.